Multimaterial 4D printing with a tunable bending model. (1st June 2023) - Zolfagharian, Ali; Jarrah, Hamid Reza; S Xavier, Matheus; Rolfe, Bernard; Bodaghi, Mahdi
Abstract: Shape-memory polymer (SMP)-based functional structures may now be produced more efficiently via four-dimensional (4D) printing, benefiting from the recent advances in multi-material three-dimensional printing technologies. Composite material design using 4D printing has opened new possibilities for customizing the shape memory property of smart polymers. This work studies a design strategy to harness desirable morphing by 4D printing multimaterial composites with a focus on the detailed finite element (FE) procedure, experimental results, and soft robotic application. Composites with bilayer laminates consisting of a SMP and a flexible elastomer are constructed with variable thickness ratios to control the self-bending of the composite. FE simulations are used to understand the underlying processes of composite materials and to generate accurate predictions for the experimental results, which reduces cost and development time. The application of 4D printing and multi-material composite programming is demonstrated with a soft robotic gripper for manipulating fragile objects.